Mranaos of Taraka and the Lake Lanao region, 1639-1913 - Usodan, Aminah Pado
American occupation of Lanao focused on the conquest of the Lake Lanao area that had remained independent from foreign rule since Spanish time. However, events changed from 1901 to 1913, when the Americans moved towards the conquest of the lake Mranaos. Literatures concerning this deal on resistance on the southern sides of the lake where the first military expeditions were dispatched from 1901 to 1913. Thereafter, the action shifted to the eastern sides where the Taraka Mranaos would figure prominently from 1907 to 1913. However, this has never been given the attention that it deserves in historical research, which calls for a balanced view of resistance. The study aims to know the factors, motives, forms, and outcomes of resistance by the Taraka Mranaos from 1901- 1913, using the concepts of tindeg and jihad and related ones for analysis. Although direct American rule precipitated the resistance, that is tindeg, along side maratabat, and jihad against saruang a tao for freedom of religion and Mranao-ness, defined in terms of Islam and the precepts of andang sa muna and amonen na rawaten,motivated resistance. Resistance had two forms, kota wars and kapadalan or hit and run tactics. The defeat of kota wars in the lake since 1903 led to a shift in strategy, from kota wars to kapadalan or hit and run tactics. The destruction of the kotas, the prohibition of the construction of new ones, the capture and destruction of artillery and ammunition, the death of many leaders, the scattering of resistors into small hit and run groups, the criminalization of kapadalan, and the "pacification" of Lanao were among the outcomes of the resistance. A disarmamaent policy that sought to impose peace and order in the Moro Province succeeded in effecting the surrender and/or arrest of resistors. Thus, while the rest of Lanao was considered "pacified" by 1903, Taraka resistance represented struggle against direct American domination until 1913.